Values of health and sports achievements in the structure of social identity of modern Russian youth - Yumkina E.A.; Volkov V.V.; Kochegova L.E. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to determine the place of the values of sports achievements and health in the structure of social identity of student youth. Methods and structure of the study. Students of the humanities and technical fields of universities in St. Petersburg (n=200) participated in the scientific work. The average age is 20 years, boys – 31%, girls – 69%. The work included the questionnaire «Value Orientations-36» (V.N. Kunitsyna); ISSP civic identity scales (adapted by L.K. Grigoryan); scale for express assessment of feelings associated with ethnicity (N.M. Lebedeva); multifactorial personality questionnaire «STEEL» (V.N. Kunitsyna). Results and conclusions. The values of sports achievements and health are a basic part of the social identity of young people. On their basis, young people realize their own involvement in culture, inclusion in the course of its historical time. Pride in sports achievements, as an element of civic identity, forms a semantic vector connecting youth with the older generation and traditions. The value of health sets a benchmark for a more responsible construction of interpersonal relationships, in particular, love relationships, and actualizes the ability to measure one’s strengths with one’s aspirations. The obtained result opens up space for improving educational work with university students, reflecting more targeted targets for pedagogical influence.